MVP Architecture Applied to an Efficient Development of an Interactive Software for Circle Study - Anca-Elena Iordan (Current Overview on Science and Technology Research Vol. 1, 2022)
This chapter includes the essential steps required for oriented object implementation of an interactive software used in the study of circle. The software modelling is accomplished through specific UML diagrams representing the stages of analysis, design and implementation, the software development thus being presented in a concrete way. The design needs to be suitable to the problem, but also universal enough to be able to add ulterior requirements. In the process of development an interactive educational software, architecture represents more than likely the most meaningful element that can distort its quality. The implementation of presented educational software is refined by usage of the "Model-View-Presenter" architectural pattern. The software is very useful to both students and teachers because the mathematics, especially geometry, is difficult to understand for most students.